A plastic filling masterbatch and preparation method thereof
By using talc composite materials and high-density polyethylene toughening components in plastic filler masterbatches, the problem of poor compatibility between mineral filler and polypropylene is solved, and the mechanical properties, flame retardant properties and low odor characteristics of plastic masterbatches are improved.
Patent Information
- Application Number
- CN202410127168.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-30
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-01-30
AI Technical Summary
The mineral filler and polypropylene in existing plastic filled masterbatches have poor compatibility, which affects the performance of composite materials.
Using talc composite material and high-density polyethylene toughening components, the compatibility of talc powder and polypropylene is improved by loading an organometallic frame and grafting polypropylene in talc powder, and the interfacial bonding is improved through the melt extrusion process.
It significantly improves the mechanical properties, flame retardant properties and low odor characteristics of the plastic masterbatch, and improves the compatibility of mineral fillers and polypropylene.
Smart Images

Figure BDA0004688665940000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of plastics, and in particular relates to a plastic filling masterbatch and a preparation method thereof. Background Art
[0002] Plastic filler masterbatch is an additive in the plastic processing process. It is mainly made of inorganic powder, carrier resin and modified additives through extrusion granulation to obtain filler masterbatch that can meet the requirements of plastic product molding process. It can reduce the raw material cost of plastic products, save synthetic resin, improve the physical properties of plastic products, and improve processing efficiency.
[0003] In recent years, polypropylene materials have been widely used in automobiles, home appliances, machinery manufacturing and other fields due to their simple synthesis process, light weight, good corrosion resistance and good mechanical properties. However, pure PP has poor impact resistance. Filling and modifying PP with mineral filler masterbatch can greatly improve the dimensional stability, rigidity, thermal stability and low-temperature cracking of PP composite materials. Commonly used mineral fillers include calcium carbonate, talc, mica, wollastonite, etc., but these mineral fillers have large free energy, are easy to agglomerate, and have high surface polarity and poor compatibility with organic polymers, which affects the performance of composite materials. Therefore, how to improve the compatibility of mineral fillers with polypropylene and obtain corresponding plastic filling masterbatch is a technical problem that needs to be solved at present. Summary of the invention
[0004] The purpose of the present invention is to provide a plastic filling masterbatch and a preparation method thereof, so as to solve the problem of poor compatibility between mineral fillers and polypropylene in the existing filling masterbatch.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A plastic filling masterbatch, comprising the following raw materials in parts by weight:
[0007] 15-40 parts of polypropylene resin, 50-80 parts of talc composite material, 3-8 parts of high-density polyethylene toughening component, 4-6 parts of compatibilizer, and 1-2 parts of lubricant.
[0008] The method for preparing the above-mentioned plastic filling masterbatch comprises the following steps:
[0009] The raw materials are weighed according to the proportion, and the polypropylene resin, talcum powder composite material, high-density polyethylene toughening component, compatibilizer and lubricant are added into an internal mixer and mixed evenly to obtain a mixture, and the mixture is added into a twin-screw extruder for extrusion granulation at an extrusion granulation temperature of 160-180° C. to obtain a plastic filling masterbatch.
[0010] Furthermore, the banburying temperature is 180-210° C., and the banburying time is 0.5-1 h.
[0011] Among them, the talc composite material is a composite product composed of talc and organic metal framework.
[0012] Furthermore, the steps for preparing the talc composite material are as follows:
[0013] Talc was added to DMF, stirred at room temperature for 30 minutes, then ferric chloride hexahydrate and 2-aminoterephthalic acid were added, acetic acid was added after ultrasonication for 30 minutes, and the mixture was transferred to a polytetrafluoroethylene hydrothermal autoclave after magnetic stirring for 10 minutes, reacted at 120°C for 5-7 hours, cooled to room temperature, filtered, and the filter cake was washed and dried in a vacuum oven at 60°C to constant weight to obtain a talc composite material.
[0014] Aiming at the problem of poor compatibility between talc and polypropylene, the present invention uses talc as a base material, 2-aminoterephthalic acid and ferric chloride hexahydrate as raw materials, and loads an organic metal framework on the talc to obtain a talc composite material. The presence of the organic framework can improve the compatibility between the talc and the polypropylene. During the melt extrusion process, the active amino group can react with the maleic anhydride grafted polypropylene to improve the interface bonding between the talc and the polypropylene, and give the plastic masterbatch excellent mechanical properties. In addition, the organic metal framework has a large specific surface area and abundant active sites, which is conducive to improving the flame retardant property and low odor property of the composite material.
[0015] Furthermore, the usage ratio of talc, DMF, ferric chloride hexahydrate, 2-aminoterephthalic acid and acetic acid is 4-6 g:40-60 mL:6.2 g:4.2 g:20 mL.
[0016] Furthermore, the particle size D50 of the talc is 10-15 μm.
[0017] Furthermore, the steps for preparing the high-density polyethylene toughening component are as follows:
[0018] Step S1, adding dimethyl maleate and diisopropylbenzene peroxide to acetone and stirring evenly to obtain a mixed solution, placing the mixed solution and high-density polyethylene particles in a high-speed mixer for mixing, and after the acetone is completely volatilized, adding the mixed solution to a torque rheometer at a speed of 50 r / min and a temperature of 200° C. to react for 10 minutes, and then extruding and granulating through a twin-screw extruder to obtain an intermediate product;
[0019] Step S2, adding the intermediate product and xylene into a reactor, swelling at 100° C. for 30-60 min, then cooling to 50-60° C., adding solution a consisting of hydrazine hydrate and anhydrous methanol, stirring and reacting for 2-3 h, cooling to room temperature, filtering, washing the filter cake with anhydrous ethanol and drying, and obtaining a high-density polyethylene toughening component.
[0020] High-density polyethylene has a toughening effect on polypropylene, but the compatibility of the two is poor. Based on this, the present invention uses high-density polyethylene as a base material, diisopropylbenzene peroxide as an initiator, and dimethyl maleate as a grafting agent. A branch containing an ester group is introduced into the high-density polyethylene molecular chain by melt grafting, and then the ester group of the intermediate product reacts with hydrazine hydrate to obtain a high-density polyethylene containing a hydrazide branch chain. The introduction of the branched chain structure can increase the contact area between polymer molecules, which is helpful to improve the compatibility between high-density polyethylene and polypropylene, thereby effectively improving the mechanical properties of the composite material. The amino group on the hydrazide group can undergo a condensation reaction with the nitrogen atom containing a lone pair of electrons in the carbonyl group of aldehydes and ketones to generate a relatively stable hydrazone bond, thereby achieving the purpose of removing aldehyde and ketone VOC gases.
[0021] Furthermore, in step S1, the mass ratio of dimethyl maleate, dicumyl peroxide, acetone and high-density polyethylene particles is 2:0.14-0.28:3-5:100.
[0022] Furthermore, in step S2, the usage ratio of the intermediate product, xylene, hydrazine hydrate and anhydrous methanol is 10 g:90 mL:0.4-0.6 mL:5-10 mL, and the mass fraction of hydrazine monohydrate in the hydrazine hydrate is 80%.
[0023] Furthermore, the extrusion temperature in step S1 is 120-180°C.
[0024] Furthermore, the compatibilizer is maleic anhydride grafted polypropylene.
[0025] Furthermore, the lubricant is one or more of calcium stearate, zinc stearate, ethylene bisstearamide and erucamide.
[0026] Furthermore, the polypropylene resin is composed of a first polypropylene resin and a second polypropylene resin in a mass ratio of 1:1, the melt index of the first polypropylene resin is 3-8g / min, the melt index of the second polypropylene resin is 10-16g / min, the melt index is determined according to GB / T3682-2000, the test temperature is 230°C and the target load is 2.16kg.
[0027] Beneficial effects of the present invention:
[0028] 1. The present invention provides a plastic filling masterbatch, which uses polypropylene resin as a carrier, talcum powder composite material and high-density polyethylene toughening component as fillers, and is used to prepare plastic products such as films, pipes, sheets, injection moldings, etc., and can improve the mechanical properties and flame retardant properties of plastic products as well as low VOC characteristics.
[0029] 2. The talc composite material of the present invention has good dispersibility in polypropylene resin, and can effectively improve the mechanical properties of plastic masterbatch. In addition, the metal organic framework on its surface has good adsorption performance for volatile compounds (VOCs), which can give the plastic masterbatch a lower odor. During the combustion process, the porous structure of the metal organic framework increases the reaction space for the active pyrolysis products of the material, thereby delaying or inhibiting the generation and emission of salt mist. The metal organic framework is pyrolyzed to form porous metal compounds, which promote the formation of a carbon layer and inhibit the release of toxic gases. The aromatic structure and nitrogen-containing groups in the organic ligands in the metal organic framework also provide a flame retardant effect. Therefore, the introduction of the talc composite material significantly improves the flame retardant properties of the plastic masterbatch.
[0030] 3. The high-density polyethylene toughening in the present invention can not only effectively play a toughening role, but also remove aldehyde and ketone VOC gases, further enhancing the mechanical properties and low odor characteristics of the plastic masterbatch. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] In the following examples and comparative examples, maleic anhydride grafted polypropylene was purchased from ExxonMobil (brand: PO1015), and high-density polyethylene was purchased from Shenhua Baotou Coal Chemical Co., Ltd., with a melt mass flow rate of 8.0 g / 10 min.
[0033] Example 1
[0034] The steps for preparing the talc composite material are as follows:
[0035] 4 g of talc (particle size D50 is 10-15 μm) was added to 40 mL of DMF, stirred at room temperature for 30 min, then 6.2 g of ferric chloride hexahydrate and 4.2 g of 2-aminoterephthalic acid were added, and 20 mL of acetic acid was added after ultrasonic treatment for 30 min. After magnetic stirring for 10 min, the mixture was transferred to a polytetrafluoroethylene hydrothermal autoclave and reacted at 120 ° C for 5 h. The mixture was cooled to room temperature and filtered. The filter cake was washed 3 times with DMF and anhydrous ethanol respectively, and finally dried in a vacuum oven at 60 ° C to constant weight to obtain a talc composite material.
[0036] Example 2
[0037] The steps for preparing the talc composite material are as follows:
[0038] 6 g of talc (particle size D50 is 10-15 μm) was added to 60 mL of DMF, and after stirring at room temperature for 30 min, 6.2 g of ferric chloride hexahydrate and 4.2 g of 2-aminoterephthalic acid were added. After ultrasonication for 30 min, 20 mL of acetic acid was added, and after magnetic stirring for 10 min, the mixture was transferred to a polytetrafluoroethylene hydrothermal autoclave and reacted at 120 ° C for 7 h. The mixture was cooled to room temperature and filtered. The filter cake was washed 3 times with DMF and anhydrous ethanol respectively, and finally dried in a vacuum oven at 60 ° C to constant weight to obtain a talc composite material.
[0039] Comparative Example 1
[0040] The comparative example is talcum powder, and the particle size D50 is 10-15 μm.
[0041] Example 3
[0042] The steps for preparing the high-density polyethylene toughening component are as follows:
[0043] Step S1, adding 2kg of dimethyl maleate and 0.14kg of diisopropylbenzene peroxide to 3kg of acetone and stirring to obtain a mixed solution, placing the mixed solution and 100kg of high-density polyethylene particles in a high-speed mixer for mixing, and after the acetone is completely volatilized, adding the mixed solution to a torque rheometer at a speed of 50r / min and a temperature of 200°C to react for 10min, and then extruding and granulating through a twin-screw extruder at a temperature of 120-180°C to obtain an intermediate product;
[0044] Step S2, adding 10 kg of the intermediate product and 90 L of xylene into a reactor, swelling at 100 ° C for 30 min and then cooling to 50 ° C, adding solution a consisting of 0.4 L of hydrazine hydrate and 5 L of anhydrous methanol, keeping warm and stirring for 2 hours, cooling to room temperature, filtering, washing the filter cake with anhydrous ethanol and then drying to obtain a high-density polyethylene toughening component, wherein the mass fraction of hydrazine monohydrate in the hydrazine hydrate is 80%.
[0045] Example 4
[0046] The steps for preparing the high-density polyethylene toughening component are as follows:
[0047] Step S1, adding 2kg of dimethyl maleate and 0.28kg of diisopropylbenzene peroxide to 5kg of acetone and stirring to obtain a mixed solution, placing the mixed solution and 100kg of high-density polyethylene particles in a high-speed mixer for mixing, and after the acetone is completely volatilized, adding the mixed solution to a torque rheometer at a speed of 50r / min and a temperature of 200°C to react for 10min, and then extruding and granulating through a twin-screw extruder at a temperature of 120-180°C to obtain an intermediate product;
[0048] Step S2, adding 10 kg of the intermediate product and 90 L of xylene into a reactor, swelling at 100 ° C for 60 min and then cooling to 60 ° C, adding solution a consisting of 0.6 L of hydrazine hydrate and 10 L of anhydrous methanol, keeping warm and stirring for 3 hours, cooling to room temperature, filtering, washing the filter cake with anhydrous ethanol and then drying to obtain a high-density polyethylene toughening component, wherein the mass fraction of hydrazine monohydrate in the hydrazine hydrate is 80%.
[0049] Comparative Example 2
[0050] This comparative example is high density polyethylene.
[0051] Example 5
[0052] A plastic filling masterbatch, comprising the following raw materials in parts by weight:
[0053] 15 parts of polypropylene resin, 50 parts of the talc composite material of Example 1, 3 parts of the high-density polyethylene toughening component of Example 3, 4 parts of maleic anhydride grafted polypropylene, and 1 part of lubricant.
[0054] The method for preparing the above-mentioned plastic filling masterbatch comprises the following steps:
[0055] Weigh the raw materials according to the ratio, add the polypropylene resin, talcum powder composite material, high-density polyethylene toughening component, compatibilizer and lubricant into an internal mixer, mix at 180°C for 1 hour to obtain a mixture, add the mixture into a twin-screw extruder for extrusion granulation at a temperature of 160-180°C to obtain a plastic filling masterbatch.
[0056] Among them, the lubricant is calcium stearate, the polypropylene resin is composed of a first polypropylene resin and a second polypropylene resin in a mass ratio of 1:1, the melt index of the first polypropylene resin is 3g / min, the melt index of the second polypropylene resin is 10g / min, the melt index determination method is GB / T3682-2000, the test temperature is 230°C and the target load is 2.16kg.
[0057] Example 6
[0058] A plastic filling masterbatch, comprising the following raw materials in parts by weight:
[0059] 30 parts of polypropylene resin, 65 parts of the talc composite material of Example 1, 5 parts of the high-density polyethylene toughening component of Example 4, 5 parts of maleic anhydride grafted polypropylene, and 1.5 parts of lubricant.
[0060] The method for preparing the above-mentioned plastic filling masterbatch comprises the following steps:
[0061] Weigh the raw materials according to the ratio, add the polypropylene resin, talcum powder composite material, high-density polyethylene toughening component, compatibilizer and lubricant into an internal mixer, mix at 210°C for 0.5h to obtain a mixture, add the mixture into a twin-screw extruder for extrusion granulation at a temperature of 160-180°C to obtain a plastic filling masterbatch.
[0062] Among them, the lubricant is zinc stearate, the polypropylene resin is composed of a first polypropylene resin and a second polypropylene resin in a mass ratio of 1:1, the melt index of the first polypropylene resin is 5g / min, the melt index of the second polypropylene resin is 12g / min, the melt index determination method is GB / T3682-2000, the test temperature is 230°C and the target load is 2.16kg.
[0063] Example 7
[0064] A plastic filling masterbatch, comprising the following raw materials in parts by weight:
[0065] 40 parts of polypropylene resin, 80 parts of the talc composite material of Example 2, 8 parts of the high-density polyethylene toughening component of Example 4, 6 parts of maleic anhydride grafted polypropylene, and 2 parts of lubricant.
[0066] The method for preparing the above-mentioned plastic filling masterbatch comprises the following steps:
[0067] Weigh the raw materials according to the ratio, add the polypropylene resin, talcum powder composite material, high-density polyethylene toughening component, compatibilizer and lubricant into an internal mixer, mix at 210°C for 0.5h to obtain a mixture, add the mixture into a twin-screw extruder for extrusion granulation at a temperature of 160-180°C to obtain a plastic filling masterbatch.
[0068] Among them, the lubricant is ethylene bisstearamide, the polypropylene resin is composed of a first polypropylene resin and a second polypropylene resin in a mass ratio of 1:1, the melt index of the first polypropylene resin is 8 g / min, the melt index of the second polypropylene resin is 16 g / min, the melt index determination method is GB / T3682-2000, the test temperature is 230°C and the target load is 2.16 kg.
[0069] Comparative Example 3
[0070] Compared with Example 5, the talc composite material in Example 5 is replaced by the material in Comparative Example 1, and the remaining raw materials and preparation process are the same as in Example 5.
[0071] Comparative Example 4
[0072] Compared with Example 7, the high-density polyethylene toughening component in Example 7 is replaced with the substance in Comparative Example 2, and the remaining raw materials and preparation process are the same as in Example 7.
[0073] The plastic masterbatch obtained from Example 5 to Example 7 and Comparative Example 3 to Comparative Example 4 was injection molded into a standard plastic specimen, and the tensile strength was tested with reference to the standard GB / T 1040, in MPa; the cantilever beam notched impact strength was tested with reference to the standard GB / T1843, in KJ / m 2 ; The odor was tested according to VDA 270 (20 / 40°C), and the oxygen index was tested according to GB / T 2406.1-2008. The test results are shown in Table 1:
[0074] Table 1
[0075]
[0076] It can be seen from the data recorded in Table 1 that, compared with Comparative Examples 3 and 4, the plastic filling masterbatches obtained in Examples 5, 6 and 7 have good mechanical properties, flame retardant properties and low odor properties, indicating that the filling masterbatch prepared by the present invention is of high quality and has significant practical value.
[0077] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0078] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A plastic filling masterbatch, characterized in that: It includes the following raw materials in parts by weight: 15-40 parts of polypropylene resin, 50-80 parts of talc composite material, 3-8 parts of high-density polyethylene toughening component, 4-6 parts of compatibilizer, 1-2 parts of lubricant; Among them, the talc composite material is a composite product composed of talc and an organic metal framework; The steps for preparing the talc composite material are as follows: The talc powder was added to DMF, stirred at room temperature for 30 minutes, and then ferric chloride hexahydrate and 2-aminoterephthalic acid were added. After ultrasonication for 30 minutes, acetic acid was added, and the mixture was transferred to a polytetrafluoroethylene hydrothermal reactor after magnetic stirring for 10 minutes. The mixture was reacted at 120°C for 5-7 hours, cooled to room temperature, filtered, and the filter cake was washed and dried in a vacuum oven at 60°C to constant weight to obtain a talc powder composite material. The steps for preparing the high-density polyethylene toughening component are as follows: Step S1, adding dimethyl maleate and diisopropylbenzene peroxide to acetone and stirring to obtain a mixed solution, mixing the mixed solution with high-density polyethylene particles, and after the acetone is completely volatilized, adding the mixed solution to a torque rheometer and reacting at 200° C. for 10 minutes, and then extruding and granulating to obtain an intermediate product; Step S2, adding the intermediate product and xylene into a reactor, swelling at 100° C. for 30-60 min, then cooling to 50-60° C., adding solution a consisting of hydrazine hydrate and anhydrous methanol, stirring and reacting for 2-3 h, cooling to room temperature, filtering, washing the filter cake with anhydrous ethanol and drying, and obtaining a high-density polyethylene toughening component.
2. A plastic filling masterbatch according to claim 1, characterized in that: The usage ratio of talc, DMF, ferric chloride hexahydrate, 2-aminoterephthalic acid and acetic acid is 4-6g:40-60mL:6.2g:4.2g:20mL.
3. A plastic filling masterbatch according to claim 1, characterized in that: The particle size D50 of talc is 10-15 μm.
4. The plastic filling masterbatch according to claim 1, characterized in that: In step S1, the mass ratio of dimethyl maleate, dicumyl peroxide, acetone and high-density polyethylene particles is 2:0.14-0.28:3-5:
100.
5. The plastic filling masterbatch according to claim 1, characterized in that: In step S2, the usage ratio of the intermediate product, xylene, hydrazine hydrate and anhydrous methanol is 10 g:90 mL:0.4-0.6 mL:5-10 mL, and the mass fraction of hydrazine monohydrate in the hydrazine hydrate is 80%.
6. The method for preparing a plastic filling masterbatch according to claim 1, characterized in that: The following steps are involved: The raw materials are weighed according to the proportion, and the polypropylene resin, talcum powder composite material, high-density polyethylene toughening component, compatibilizer and lubricant are added into an internal mixer and mixed evenly to obtain a mixture, and the mixture is added into a twin-screw extruder for extrusion granulation at an extrusion granulation temperature of 160-180° C. to obtain a plastic filling masterbatch.
Citation Information
Patent Citations
Polypropylene composite material for automotive interior parts and production process of polypropylene composite material for automotive interior parts
CN108047560A
Easy-to-spray composition suitable for thin-wall injection molding and preparation method of easy-to-spray composition
CN112778650A